PENGEMBANGAN MEDIA PEMBELAJARAN IQRA BERBASIS CANVA PADA ANAK USIA DINI ( PAUD ) - Rima Sahaya; Aan Hendrayana; Rudi Haryadi (STKIP Subang, 2023)
Canva is application design graphics used For make social media graphics , presentations , posters, documents And other visual content . In this digital era, Canva media very help educators For used as internal media learning for more interesting And children can increase results learn more Good. In matter This researcher try make letters hijaiyah using flashcards from canva . Method study This use method qualitative . From the results study activity learning before And after using Canva media there is difference results percentage seen from the data obtained through interview to colleague colleague And participant educate. With thereby participant educate more like learning using Canva media Because easy understood And more pleasant .